Non-Verbal Communication in the Tom and Jerry Film - Ariyati, Yumi; Catherine, Sarkissian (Semantik: Journal of Social, Media, Communication, and Journalism, 2024)
The purpose of this writing is to delve deeper into nonverbal and verbal communication in the cartoon film "Tom and Jerry." In this research, a qualitative research method is used with the semiotic analysis model of Charles Sanders Peirce. Data collection techniques include document analysis and indirect observation. In the film Tom and Jerry, the researchers found nonverbal communication that has several functions, namely repetition, accentuation, complementation, contradiction, substitution, and regulation. In nonverbal communication, there are body movements, touch, vocalics, and others. In the film Tom and Jerry, there is 99% nonverbal communication. In this film, Tom and Jerry mostly always fight and communicate nonverbally. Although this film has no sound, most children and even adults find it entertaining.